Double Resonance Characteristic of Photonic Crystal Structure with Defect Metal Layer - Negara, Teguh Puja; Supian, Sudradjat; Subiyanto, Subiyanto; Mustafa, Mohd Kamarulzaki (semarak ilmu, 2025)
The optical response of the photonic crystal structure has been analyzed using the Finite Difference Frequency Domain (FDFD) method. Simulation using this method aims to analyze the characteristics of light transmission when interacting with related structure. The results of the study of photonic crystal structures with two defects show that there are two transmittance bands called double resonances at two specific wavelengths. Changes in the resonance peak with respect to the variations of refractive index in the second defect layer resulted in a linear change with significant sensitivity. For photonic crystals with two defects, the first defect is a metal layer and the second defect is material sensing, which produces double resonance with a sensitivity of 7,825 and 3,2675, while for photonic crystals with the first defect, a dielectric layer, and the second defect is material sensing, produces single resonance with a sensitivity of 2,022. The choice of the first defect is that the metal layer is quite important, in addition to producing greater sensitivity, it also produces a field enhancement between the dielectric and the metal layer which is called surface plasmon resonance (SPR). The sensitivity value can also be set by determining the thickness of the second defect layer. These results can be used as a standard for fabrication and developed for sensor applications.